The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1177/1352458508094643
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphism is associated with reduced disability in multiple sclerosis

Abstract: Ultraviolet radiation (UVR) may contribute to multiple sclerosis (MS) outcome by a mechanism involving vitamin D and the vitamin D receptor (VDR). In 512 patients with MS duration of 10 or more years, we studied the association of VDR single nucleotide polymorphisms (A/G(1229), C/G(3444), G/A(3944), CC(20965), CC(30056), F/f(30875), C/T(48200), T/t(65013)) with outcome or disability. ff(30875) frequency was lower in cases with EDSS > or = 6.0 than with scores < 6.0 (odds ratio = 0.38, 95% CI = 0.20-0.70). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…In 512 patients with MS of at least 10 years duration, study of outcome or disability with the association of VDR single nucleotide polymorphisms (A/G(1229), C/G (3444), G/A(3944), CC(20965), CC(30056), F/f(30875), C/T(48200), T/t (65013)), showed that ff (30875) frequency was lower in cases with EDSS > or = 6.0 than with scores< 6.0 [52].…”
Section: Vitamin D Receptormentioning
confidence: 96%
“…In 512 patients with MS of at least 10 years duration, study of outcome or disability with the association of VDR single nucleotide polymorphisms (A/G(1229), C/G (3444), G/A(3944), CC(20965), CC(30056), F/f(30875), C/T(48200), T/t (65013)), showed that ff (30875) frequency was lower in cases with EDSS > or = 6.0 than with scores< 6.0 [52].…”
Section: Vitamin D Receptormentioning
confidence: 96%
“…The short VDR encoded by the FokI f variant reportedly has higher transcriptional activation function [119,120]. In British populations, the Fok1 Fencoded long VDR was associated with higher MS risk in males, but not females [121], whereas the FokI f -encoded short VDR was associated with reduced disability a decade after disease onset [122].…”
Section: The Vdr Genementioning
confidence: 98%
“…The evidence for an association between the development of MS and polymorphisms in the VDR is mixed, with some finding an association [127129] but others finding no association [125,126,130132]. In addition, interactions between VDR polymorphisms and HLA-DR15 [133], exposure to sunlight [130] or dietary vitamin D intake [126] have been observed, but these have not yet been confirmed.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%